Pengukuran Risiko Sistemik di Negara-negara Berkembang ASIA-7 - Harun Arasyid; Rinda Siaga Pangestuti (Ekonomis: Journal of Economics and Business, 2020)
The research on systemic risk is important to carry out in view of the alleged repetition of the eight-year crisis cycle affecting the market. The data of average stock returns calculation in almost all sample countries was negative in 2011 and repeated again in 2019 that the average banking stock returns in Malaysia, Thailand, the Philippines, Pakistan, and Sri Lanka showed a negative value. Even since 2018, the Philippines, Pakistan and Sri Lanka have consistently been shown to experience negative average returns. Systemic risk measurement is done by two methods, namely ΔCoVaR and MES. Furthermore, this research is very supportive and has been in line with the research roadmap of Islamic University 45 which states that in 2018-2026 the academic research is more focused on the application of regional technology and social engineering models that instead the products in the form of policies to then develop international standard research. In this study, the sample of countries used covers the Asian region, the topic discussed is a very important issue in the financial sector considering that systemic risk cannot be eliminated. In general, there are three findings that are explained from the results of the ΔCoVaR calculation that: (a) most developing countries experienced a decrease in their contribution to systemic events after the 2008 global crisis period; (b) large banks make the biggest contribution to systemic events, except for banks in Malaysia both small and large banks make equal contributions to systemic events; (c) There is a potential for systemic event to increase after 2019 that the contribution to systemic events by individual banks in the Philippines, Indonesia, Sri Lanka show an upward trend in the past year so that risk mitigation measures need to be taken in the form of policies and analysis of banking financial performance and global economic conditions. Based on the overall MES calculation the bank contributes more than 50% of potential systemic events to the system.